A novel regulatory element between the human FGA and FGG genes - Fish, Richard J; Neerman-Arbez, Marguerite (Thrombosis and haemostasis, 2012)
High circulating fibrinogen levels correlate with cardiovascular disease (CVD) risk. Fibrinogen levels vary between people and also change in response to physiological and environmental stimuli. A modest proportion of the variation in fibrinogen levels can be explained by genotype, inferring that variation in genomic sequences that regulate the fibrinogen genes ( FGA , FGB and FGG ) may affect hepatic fibrinogen production and perhaps CVD risk. We previously identified a conserved liver enhancer in the fibrinogen gene cluster (CNC12), between FGB and FGA . Genome-wide Chromatin immunoprecipitation-sequencing (ChIP-seq) demonstrated that transcription factors which bind fibrinogen gene promoters also interact with CNC12, as well as two potential fibrinogen enhancers (PFE), between FGA and FGG . Here we show that one of the PFE sequences has potent hepatocyte enhancer activity. Using a luciferase reporter gene system, we found that PFE2 enhances minimal promoter- and FGA promoter-driven gene expression in hepatoma cells, regardless of its orientation with respect to the promoters. A region within PFE2 bears a short series of conserved nucleotides which maintain enhancer activity without flanking sequence. We also demonstrate that PFE2 is a liver enhancer in vivo, driving enhanced green fluorescent protein expression in transgenic zebrafish larval livers. Our study shows that combining public domain ChIP-seq data with in vitro and in vivo functional tests can identify novel fibrinogen gene cluster regulatory sequences. Variation in such elements could affect fibrinogen production and influence CVD risk.